Review: Porous Metal Filters and Membranes for Oil–Water Separation - Wang, Huiquan; Hu, Xiaoyue; Ke, Zunwen; Du, Ce Zhi; Zheng, Lijuan; Wang, Chengyong; Yuan, Zhishan (Nanoscale research letters, 2018)
In recent years, oil–water separation has been widely researched to reduce the influences of industrial wastewater and offshore oil spills. A filter membrane with special wettability can achieve the separation because of its opposite wettability for water phase and oil phase. In the field of filter membrane with special wettability, porous metal filter membranes have been much investigated because of the associated high efficiency, portability, high plasticity, high thermal stability, and low cost. This article provides an overview of the research progress of the porous metal filter membrane fabrication and discusses the future developments in this field.